Microsomal Prostaglandin E Synthase-1 in Rheumatic Diseases - Korotkova, Marina; Jakobsson, Per J. (Frontiers in Pharmacology, 2011)
Microsomal prostaglandin E synthase-1 (mPGES-1) is a well recognized target for the development of novel anti-inflammatory drugs that can reduce symptoms of inflammation in rheumatic diseases and other inflammatory conditions. In this review, we focus on mPGES-1 in rheumatic diseases with the aim to cover the most recent advances in the understanding of mPGES-1 in rheumatoid arthritis, osteoarthritis and inflammatory myopathies. Novel findings regarding regulation of mPGES1 cell expression as well as enzyme inhibitors are also summarized.